Effectiveness of School-Based Oral Health Education Programs in Reducing Dental Caries Among School Children of Lucknow City - Dr. Shitanshu Malhotra; Dr. Diksha Bharti; Dr. Ashish Kumar Dwivedi; Dr. Harsh Aryan (The Bioscan, 2025)
Introduction:Dental caries has profound implications for children's overall health and well-being.Beyond the immediate physical effects, dental caries can also have psychological and social consequences. Children with visible dental decay or missing teeth may experience embarrassment, low self-esteem, and social isolation. These psychosocial impacts underscore the importance of addressing dental caries not just as a medical issue, but as a significant factor affecting a child's overall quality of life.Aims & Objectives: The aim of study isto evaluate the effectiveness of a school-based oral health education program in reducing dental caries among school-going children aged 12 to 15 years of Lucknow city.Materials & Methods:A quasi-experimental, before-and-after design to assess the effectiveness of school-based oral health education programs in reducing dental caries among 12 to 15 years oldschool children. Data collection occurred at three time points: baseline, 3 months, and 6 months post-intervention, with a follow-up study conducted one year after the baseline assessment in 210 participants. Descriptive statistics were used to summarize the data, and inferential statistics were used to determine the effectiveness of the intervention.Results:The results indicate that the school-based oral health education program significantly reduced both DMFT scores and gingival index scores in the intervention group over 12 months. The intervention group showed a significant reduction in DMFT scores from 3.20 to 2.10 (t = -12.34, p < 0.001) and in gingival index scores from 1.80 to 1.20 (t = -10.45, p < 0.001).Conclusion: The study concluded that oral health education could play a crucial role in school health programs, providing an effective tool for reducing caries risk, improving gingival health, and promoting better oral hygiene practices among children.